Analysis of Short Tandem Repeat and Single Nucleotide Polymorphism Loci From Single-Source Samples Using a Custom HaloPlex Target Enrichment System Panel. (June 2016) - Wendt, Frank R.; Zeng, Xiangpei; Churchill, Jennifer D.; King, Jonathan L.; Budowle, Bruce
Abstract : Abstract: Short tandem repeats and single nucleotide polymorphisms (SNPs) are used to individualize biological evidence samples. Short tandem repeat alleles are characterized by size separation during capillary electrophoresis (CE). Massively parallel sequencing (MPS) offers an alternative that can overcome limitations of the CE. With MPS, libraries are prepared for each sample, entailing target enrichment and bar coding, purification, and normalization. The HaloPlex Target Enrichment System (Agilent Technologies) uses a capture-based enrichment system with restriction enzyme digestion to generate fragments containing custom-selected markers. It offers another possible workflow for typing reference samples. Its efficacy was assessed using a panel of 275 human identity SNPs, 88 short tandem repeats, and amelogenin. The data analyzed included locus typing success, depth of sequence coverage, heterozygote balance, and concordance. The results indicate that the HaloPlex Target Enrichment System provides genetic data similar to that obtained by conventional polymerase chain reaction-CE methods with the advantage of analyzing substantially more markers in 1 sequencing run. The genetic typing performance of HaloPlex is comparable to other MPS-based sample preparation systems that utilize primer-based target enrichment. Abstract : Supplemental digital content is available in the text.